Rare-Earth Elements as Natural Tracers for In Situ Remediation of Groundwater - Wilkin, Richard T. (Environ Sci Technol, 2020)
The utility of rare-earth elements (REEs) as natural geochemical tracers for the analysis of groundwater remediation was examined in several example permeable reactive barriers (PRBs). The PRBs utilize zero-valent iron and organic carbon plus limestone mixtures for contaminant treatment. Zero-valent iron removed REEs from groundwater to below detection levels (2–4 ng/L) and subsequent rebound of REE concentrations in regions down-gradient of the treatment zones was not observed. In addition, REE concentrations within and down-gradient of an organic carbon/limestone PRB were significantly reduced to <1% of influent levels. Thus, REEs are sensitive tracers for evaluating the interaction of groundwater with materials placed in the subsurface for contaminant remediation. Analysis of geochemical tracers for understanding in situ remediation becomes important in situations where down-gradient contaminant concentrations fail to decrease within expected timeframes. The field data indicated that increased solid-phase partitioning of REEs occurred with increasing pH and heavy REEs were preferentially removed compared to light REEs in ZVI systems. In the organic carbon PRB, unexpected negative europium anomalies were observed, revealing new information about redox conditions within the treatment zone. REE concentrations and shale-normalized profiles can be used as natural tracers to better understand in situ technologies for groundwater remediation.